The Effectiveness of Social Assistance Programs in Reducing EconomicInequality - Widiana Indah Permata; Jooner Rambe (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Economic inequality remains a fundamental challenge in Indonesia's development process. This study analyzes the effectiveness of social assistance programs in reducing economic inequality in Indonesia from 2019 to 2024. Social assistance programs such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), and Direct Cash Assistance (BLT) have become the government's primary instruments for addressing poverty and inequality. Using secondary data from the Central Statistics Agency (BPS) and the Ministry of Social Affairs, this research evaluates the impact of social assistance on the decline in the Gini ratio and poverty rates. The results show that social assistance programs make a significant contribution to reducing economic inequality, with the Gini ratio decreasing from 0.388 in 2023 to 0.379 in March 2024. Poverty rates also declined from 16.66% in 2004 to 8.57% in September 2024. However, disparities between urban and rural areas persist. The PKH and BPNT programs proved more effective, with graduation rates reaching 8% in 2019. This research recommends improving coordination between programs and refining targeting systems to achieve optimal results.